Hubungan Patron-Klien Dalam Rekrutmen Calon Anggota Legislatif Partai Gerindra Kota Tidore Kepulauan Tahun 2014 - Mochdar Soleman; Kamaruddin Salim (Populis : Jurnal Sosial dan Humaniora, 2022)
The existence of political parties in Indonesia has an important role in the democratic system. Political parties have several functions and one of them is political recruitment, namely a selection of candidates for legislative members to produce a quality leader. This study discusses the recruitment strategy by the Gerindra Party in conducting the regeneration of members of the Gerindra Party in Tidore Islands City. This study uses James Scott's Patron-Client Theory and Michael Rush and Philip Althoff's Political Recruitment Theory. The data in this study were obtained through interviews with party leaders and literature studies. This study describes that the Gerindra Party Branch Board of Tidore Islands City conducts political recruitment with a patron-client pattern. Where, patrons are associated with former activists, retirees and businessmen who have an organized mass, influence and economic capital. And clients, namely community groups who have social and cultural closeness will follow the political choices of their patrons. This study shows that the strategy model for recruiting legislative candidate figures from activists, retirees and entrepreneurs is still a popular strategy, but ignores the process of strengthening the resources of the party cadres themselves. This, of course, led to a crisis of regeneration within the party's internal.Keberadaan partai politik di Indonesia memunyai peran penting dalam sistem demokrasi. Partai politik mempunyai beberapa fungsi dan salah satunya ialah rekrutmen politik, yaitu seleksi calon anggota legislatif untuk mencetak seorang pemimpin berkualitas. Penelitian ini membahas tentang strategi rekrutmen oleh Partai Gerindra dalam melakukan kaderisasi anggota Partai Gerindra di Kota Tidore Kepulauan. Penelitian ini menggunakan Teori Patron-Klien James Scott dan Teori Rekrutmen Politik Michael Rush dan Philip Althoff. Data dalam penelitian ini diperoleh melalui wawancara ketua partai dan studi kepustakaan. Penelitian ini menguraikan bahwa Dewan Pimpinan Cabang Partai Gerindra Kota Tidore Kepulauan melakukan rekrutmen politik dengan pola patron-klien. Di mana, patron diasosiasikan dengan mantan aktivis, pensiunan dan pengusaha yang mempunyai massa teroganisir, pengaruh serta modal ekonomi. Dan klien yakni kelompok masyarakat yang mempuyai kedekatan secara sosial dan kultural akan mengikuti pilihan politik patronnya. Dalam penelitian ini menunjukkan model strategi rekrutmen figur calon anggota legislatif dari kalangan aktivis, pensiunan dan pengusaha masih menjadi strategi yang popular, namun mengabaikan proses penguatan sumber daya dari kader partai sendiri. Hal ini, tentunya menimbulkan krisis kaderisasi dalam internal partai.